The Role and Mechanism of AMIGO3 in the Formation of Aberrant Neural Circuits After Status Convulsion in Immature Mice - Li, Xue; Pan, Yanan; Gui, Jianxiong; Fang, Zhixu; Huang, Dishu; Luo, Hanyu; Cheng, Li; Chen, Hengsheng; Song, Xiaojie; Jiang, Li (Frontiers in Molecular Neuroscience, 2021)
Leucine rich repeat and immunoglobulin-like domain-containing protein 1 (LINGO-1) has gained considerable interest as a potential therapy for demyelinating diseases since it inhibits axonal regeneration and myelin production. However, the results of clinical trials targeted at LINGO-1 have been unsatisfactory. Amphoterin-induced gene and open reading frame-3 (AMIGO3), which is an analogue of LINGO-1, might be an alternative therapeutic target for brain damage. In the present study, we investigated the effects of AMIGO3 on neural circuits in immature mice after status convulsion (SC) induced by kainic acid. The expression of both AMIGO3 and LINGO-1 was significantly increased after SC, with levels maintained to 20 days after SC. Following SC, transmission electron microscopy revealed the impaired microstructure of myelin sheaths and Western blot analysis showed a decrease in myelin basic protein expression, and this damage was alleviated by downregulation of AMIGO3 expression. The ROCK/RhoA signaling pathway was inhibited at 20 days after SC by downregulating AMIGO3 expression. These results indicate that AMIGO3 plays important roles in seizure-induced damage of myelin sheaths as well as axon growth and synaptic plasticity via the ROCK/RhoA signaling pathway.